Managing school committee partnerships for facility maintenance: a poac analysis in two indonesian primary schools - Yudah Ardiansyah; Suharyanto H. Soro (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study analyzes the implementation of POAC management functions (Planning, Organizing, Actuating, Controlling) in school committee partnerships for maintaining educational facilities and infrastructure in two elementary schools with different characteristics. The research employed a qualitative approach with case study method at SDN Binabudi Cipanas and SDN Caringin Nunggal Pacet. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using Miles and Huberman's interactive model. The results show significant differences in POAC implementation between the two schools. SDN Binabudi Cipanas demonstrated participatory planning (90% program realization), clear organizing (3-5 day response time), effective actuating (40-50 participants per activity), and structured controlling. In contrast, SDN Caringin Nunggal Pacet showed reactive planning (80% emergency activities), ambiguous organizing (2-3 week response time), limited actuating (15-20 participants), and informal controlling (only 20% of parents felt informed). The effectiveness of school committee partnerships depends heavily on the integrated application of all four POAC functions. This research produces a conceptual model that unifies previous findings on collaboration, coordination, participation, and sustainability into a dynamic POAC framework. The practical implication is that partnership improvement must focus on strengthening the entire management sequence simultaneously.